Trophic Status Is Associated With Community Structure and Metabolic Potential of Planktonic Microbiota in Plateau Lakes - Shen, Mengyuan; Li, Qi; Ren, Minglei; Lin, Yan; Wang, Juanping; Chen, Li; Li, Tao; Zhao, Jindong (Frontiers in Microbiology, 2019)
Microbes in various aquatic ecosystems play a key role in global energy fluxes and biogeochemical processes. However, the detailed patterns on the functional structure and the metabolic potential of microbial communities in freshwater lakes with different trophic status remain to be understood. We employed a metagenomics workflow to analyze the correlations between trophic status and planktonic microbiota in freshwater lakes on Yun-Gui Plateau, China. Our results revealed that microbial communities in the eutrophic and mesotrophic-oligotrophic lake ecosystems harbor distinct community structure and metabolic potential. Cyanobacteria were dominant in the eutrophic ecosystems, mainly driving the processes of aerobic respiration, fermentation, nitrogen assimilation, nitrogen mineralization, assimilatory sulfate reduction and sulfur mineralization in this ecosystem group. Actinobacteria, Proteobacteria (Alpha-, Beta-, and Gammaproteobacteria), Verrucomicrobia and Planctomycetes, occurred more often in the mesotrophic-oligotrophic ecosystems than those in the eutrophic ecosystems, and these taxa potentially mediate the above metabolic processes. In these two groups of ecosystems, a difference in the abundance of functional genes involved in carbohydrate metabolism, energy metabolism, glycan biosynthesis and metabolism, and metabolism of cofactors and vitamins significantly contribute to the distinct functional structure of microbiota from surface water. Furthermore, the microbe-mediated metabolic potentials for carbon, nitrogen and sulfur transformation showed differences in the two ecosystem groups. Compared with the mesotrophic-oligotrophic ecosystems, planktonic microbial communities in the eutrophic ecosystems showed higher potential for aerobic carbon fixation, fermentation, methanogenesis, anammox, denitrification, and sulfur mineralization, but they showed lower potential for aerobic respiration, CO oxidation, nitrogen fixation, and assimilatory sulfate reduction. This study offers insights into the relationships of trophic status to planktonic microbial community structure and its metabolic potential, and identifies the main taxa responsible for the biogeochemical cycles of carbon, nitrogen and sulfur in freshwater lake environments.